Microinvasive Glaucoma Surgery using Goniotomy as A Potential Surgical Treatment Modality in Indonesia: A Descriptive Study and Literature Review: Oral Presentation - Observational Study - Resident - Wetarini, Krisnhaliani; Rahayu, Ni Kompyang; Kusumadjaja, I Made Agus; Suryaningrum, I Gusti Ayu Ratna (Majalah Oftalmologi Indonesia, 2023)
Introduction & ObjectivesMicro-invasive glaucoma surgery with goniotomy is a recent surgical treatment modality that targetsthe trabecular outflow to maintain intraocular pressure. This study aims to describe the clinicaloutcomes of excisional goniotomy using KDB and to review the published literature regarding amodified goniotomy technique as a potential surgical treatment modality in Indonesia. MethodsA cross-sectional descriptive study was conducted in patients that underwent goniotomy stand-aloneor combined with cataract surgery. Main outcome parameters consist of visual acuity, intraocularpressure (IOP), number of glaucoma medications, and complications during post-operative follow-up. ResultsA total of 7 patients (8 eyes) were included in the study, consisting of 5 (71,4%) males and 2 (28,6%)females. The mean age of the subjects was 47.7 years. Subjects consisted of primary,pseudoexfoliative, steroid-induced, and angle-recess glaucoma. Mean pre-operative IOPmeasurements showed 20.74 mmHg with visual acuity consisting of 1 (14.3%) mild visualimpairment and 7 (85.7%) severe visual impairment. Postoperatively there was progressiveimprovement in the mean IOP to 13.81 and 11.31 mmHg on first-day and one-week follow-up,respectively. Visual improvement was observed in 2 (28.5%) with mild visual impairment, 3 (42.6%)with severe visual impairment, and 2 (28.5%) with hand movement due to complications of cornealedema following phacoemulsification. A week later, visual acuity improved to 4 (57.1%) with mildvisual impairment and 3 (42.9%) with moderate visual impairment. ConclusionGoniotomy is a simple surgical method that may be applied in Indonesia as a novel technique toprovide an effective intraocular pressure-lowering effect.